Advancing allergic rhinitis research through phenome-wide association studies: Insights from known genetic loci - Xingling Tan, MD; Zhouyouyou Xiao, MB; Yao Wen, MD; Han Liu, MD; Wei Yu, MD (World Allergy Organization Journal)
Background: Allergic rhinitis (AR) is a common chronic respiratory disease that can lead to the development of various other conditions. Although genetic risk loci associated with AR have been reported, the connections between these loci and AR comorbidities or other diseases remain unclear. Methods: This study conducted a phenome-wide association study (PheWAS) using known AR risk loci to explore the impact of known AR risk variants on a broad spectrum of phenotypes. Subsequently, linkage disequilibrium score regression (LDSC) and bidirectional two-sample mendelian randomization (TSMR) analyses were used to further analyze the genetic correlation and causal relationships between significant and potentially related phenotypes and AR. Results: The PheWAS analysis indicated significant associations between asthma, eczema, nasal polyps, hypothyroidism, and AR risk variants. Additionally, potential associations were observed with ulcerative colitis, psoriasis, chalazion, pernicious anemia, glaucoma, multiple sclerosis, arthritis, prostate cancer, varicose veins of lower extremities, and heart attack. LDSC analysis showed that only asthma, eczema, and nasal polyps have significant positive genetic correlations with AR. Furthermore, TSMR analysis revealed causal relationships between AR and asthma, eczema, and nasal polyps. Conclusion: This study highlights the impact of AR risk loci on a variety of diseases. By revealing new associations and shared genetic pathways, our findings provide valuable insights into the pathophysiology of AR and pave the way for more effective targeted interventions to manage AR and its related diseases.